2016
DOI: 10.3389/fphys.2016.00226
|View full text |Cite
|
Sign up to set email alerts
|

C-Type Natriuretic Peptide Induces Anti-contractile Effect Dependent on Nitric Oxide, Oxidative Stress, and NPR-B Activation in Sepsis

Abstract: Aims: To evaluate the role of nitric oxide, reactive oxygen species (ROS), and natriuretic peptide receptor-B activation in C-type natriuretic peptide-anti-contractile effect on Phenylephrine-induced contraction in aorta isolated from septic rats.Methods and Results: Cecal ligation and puncture (CLP) surgery was used to induce sepsis in male rats. Vascular reactivity was conducted in rat aorta and resistance mesenteric artery (RMA). Measurement of survival rate, mean arterial pressure (MAP), plasma nitric oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…via the modulation of the plasma membrane NADPH oxidase by AtPNP-A. However, neither NADPH oxidases nor peroxidases, enzymes responsible for ROS generation upon pathogen attack 67 , have been identified in our protein–protein interaction studies, although animal analogues of PNP have been shown or speculated to activate NADPH oxidase 68 , 69 . Instead, we identified CAT2 (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…via the modulation of the plasma membrane NADPH oxidase by AtPNP-A. However, neither NADPH oxidases nor peroxidases, enzymes responsible for ROS generation upon pathogen attack 67 , have been identified in our protein–protein interaction studies, although animal analogues of PNP have been shown or speculated to activate NADPH oxidase 68 , 69 . Instead, we identified CAT2 (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…Recent studies have suggested that CNP is related to inflammation. For example, CNP plasma concentrations increased in humans and rats with organ dysfunction caused by sepsis-related inflammation 38,39 . However, CNP plasma levels were indistinguishable between control and Npr2 slw/slw mice.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that other pathways that signal through cGMP may still be active. Nevertheless, activation of NO signaling and activation of NPR-B by C-type natriuretic peptide, both of which stimulate guanylate cyclase, have previously been identified as major pathophysiological signaling pathways in sepsis (55)(56)(57). Sustained activation of these pathways may account for the partial increase in cGMP in BNP-KO mice and in mice treated with SP600125 or 19B3.…”
Section: Discussionmentioning
confidence: 99%